Fundamentos para el análisis estructural en dos y tres dimensiones - Romero Martínez, Roberto Tonatiuh (My University, 2013)
Fundamentos para el análisis estructural en dos y tres dimensiones
Fundamentos para el análisis estructural en dos y tres dimensiones
Keywords: Fundamentos para el análisis estructural en dos y tres dimensiones